Systematic literature review: Theory perspective in lean manufacturing performance - Norhana, Mohd Aripin; Nawanir, Gusman; Fatimah, Mahmud; Muhammad Ashraf, Fauzi; Suhaidah, Hussain; Lee, Khai Loon (Sciendo, 2023)
This review examines the trend of applying theories in LM performance and offers the latest recapitulation of related theories in LM performance. The methodology is based on Preferred Reporting Items for Systematic Reviews (PRISMA) to search for multiple scientific information databases and to guarantee that no important study is overlooked. For the single theory, highly employed theories were the Theory of Constraints, Resource-based View/Natural Resource-based View Theory (RBV/NRBV), and Contingency Theory (CT). Meanwhile, several articles employed integrations of several theories in a publication. Concerning the year of publication, significant growth in articles with underpinned theories was published from 2020 onwards. This study offers several significant contributions to researchers to widen the knowledge related to the adaptation of theories in the field of lean performance, as research underpinned by a theory offers a solid and convincing result in investigating the research problems. The first limitation was the search string to identify the related articles, which could be extended to maximize the article search. The other limitation was the database used which was limited to the Scopus database. Despite the importance of underpinning theory in research, OM has been criticized for the inadequacies of its theory, with only one-third of OM research incorporating theory. However, a limited review was conducted on the theories used in LM performance theory. To reduce this gap, this review examines the trend of applying theories in LM performance and offers the latest recapitulation of related theories in LM performance.